Population forecasting: Guest editors' introduction - Ahlburg, Dennis A.; Land, Kenneth C. (International journal of forecasting, 1992)
An introduction to a special journal issue on population forecasting (see related abstracts in SOPODA 16:1). Topics of the articles include: cohort component methods & forecast error bounds; unique features of forecasts; the role of judgment in evaluating forecasts; time-series models, structural-equation models, & model schedules; approaches to & comparisons of forecasting; stochastic demographic forecasting; & forecasts of special populations. Directions for future research are suggested. 37 References. J. W. Stanton